An Exploratory Study on Halal Branding Among Consumers in Malaysia: Factor Analysis Technique - Norhaziah Nawai; Mohammad Noorizzuddin Nooh; Nuradli Ridzwan Shah Mohd Dali; Hartini Mohammad (Universiti Sains Islam Malaysia, 2024)
Since Malaysia is heading towards being a global Halal hub, this study is very crucial to give ideas on the receptions of Muslims consumers towards Halal branding. The objective of the research is to measure the awareness of consumers towards Halal products particularly in the food industry. The study tries to identify the factors that contribute to Halal branding using factor analysis. Consumer's data were collected based on 1075 samples from all states in Malaysia. The findings show that there are 11 factors that could contribute to Halal Branding awareness which are promotion, place, attractive and quality, Halal certification, price, product samples, market demand, SME producers, Halal certification to Muslim companies, differences between Halal certified and non-Halal certified and clean operation. Further analysis using the logistic regression found that there are six factors contribute significantly to the importance of Halal branding. The factors are attractive and quality, Halal certification, market demand, SME producers, different between Halal certified and non-certified, and clean operation.